Application of three-dimensional printing technology in renal diseases - Dai, Shuxin; Wang, Qi; Jiang, Zhiwei; Liu, Chang; Teng, Xiangyu; Yan, Songbai; Xia, Dian; Tuo, Zhouting; Bi, Liangkuan (Frontiers in Medicine, 2022)
Three-dimensional (3D) printing technology involves the application of digital models to create 3D objects. It is used in construction and manufacturing and has gradually spread to medical applications, such as implants, drug development, medical devices, prosthetic limbs, and in vitro models. The application of 3D printing has great prospects for development in orthopedics, maxillofacial plastic surgery, cardiovascular conditions, liver disease, and other fields. With in-depth research on 3D printing technology and the continuous update of printing materials, this technology also shows broad development prospects in renal medicine. In this paper, the author mainly summarizes the basic theory of 3D printing technology, its research progress, application status, and development prospect in renal diseases.